The Development of 360-Degree Video-Based Virtual Reality Learning Media to Enhance Student’s Learning Interest - Saniyah, Faridatus; Shidiq, Galih Albarra; Fikri, M. Lukman (DAS Institute, 2023)
Technology development in education has become essential for optimally, efficiently, and effectively achieving educational goals in 21st-century skills. The utilization of technology in education is relevant to the development of Society 5.0 and can be seen in the academic growth of global challenges. One of the solutions for implementing technology in education is the application of technology-based learning media, which can be developed using technological advancements, including 360-degree video-based virtual reality (V.R.). The results of this study explored that virtual reality can improve students' interactive and immersive learning experience as if they can feel the sensation of being in the environment depicted in the displayed video. Additionally, engaging learning experiences can enhance students' learning interests in primary schools. However, we suggested that students accustomed to online learning must readapt to conventional understanding in future studies. Therefore, one media that can attract students' learning interest in primary schools is 360-degree video-based virtual reality.